TATA CARA DAN PROSES PENYIDIKAN TERHADAP PELAKU TINDAK PIDANA PENCURIAN UANG MELALUI ATM DI KEPOLISIAN RESOR KOTA BESAR MEDAN - Pinem, Herry Bastian; Gultom, Maidin; Simatupang, Bachtiar (JURNAL PROINTEGRITA, 2020)
This study aims at determining and understanding the causes of money theft via ATMs in the Medan City Police Legal Area, investigators' strategy in conducting investigations of money theft via ATMs in the Medan City Police Station, the obstacles faced by Medan City Police Department investigators in handling money theft through ATMs. The data used in this study are primary data and secondary data. Primary data were obtained from the field by conducting interviews and case studies with related parties. Secondary data were obtained through library research or study documentation to get secondary data. Through this research, thoughts, doctrines, opinions or conceptual thoughts from previous studies relating to the object of study research were obtained. The results showed that the causes of theft through ATMs were economic factors, environmental factors, social factors, low religious and moral experience, educational factors, family factors, and mental illness called kleptomania. The strategy of investigating the crime of money theft through ATMs by the Medan City Police is by following up the report immediately, making an investigation warrant and an investigation warrant, conducting a crime scene by examining the results of CCTV recordings, searching for traces / fingerprints of the perpetrators at the crime scene, looking for evidence used by the offender to commit a crime and to make a crime scene sketch to be attached to the minutes of the crime scene inspection. The obstacles faced by Medan City Police investigators in investigating the crime of money theft through ATMs are the absence of CCTV installed in the ATM room, the installed CCTV has been damaged so that the picture is no longer clear, there is no trace or fingerprint of the perpetrator in the ATM room because the perpetrators used gloves and damaged the crime scene because someone had come in and out of the ATM room before the police came to inspect the crime scene.